Computer aided design of simply supported, Class 1, prestressed post-tensioned concrete beam with effective bond, in accordance with BS 5400 : 1978 / Azmi Ibrahim - Ibrahim, Azmi (1986)
A computer program in Basic Language has been developed for the design of simply-supported, Class 1 prestressed post-tensioned concrete beam with effective bond, in accordance with BS 5400 : 1978 using IBM-PC system. A design of post-tensioned concrete beam both manually and using computer is included in the report for verification. Together with this, a users guide on how to use the program has also been included. The program can be further modified to the design of Class 2 and 3; members by replacing certain requirements pertaining to each classes.